3x+3(x+1)+5=2(3x)+8

Simple and best practice solution for 3x+3(x+1)+5=2(3x)+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3(x+1)+5=2(3x)+8 equation:


Simplifying
3x + 3(x + 1) + 5 = 2(3x) + 8

Reorder the terms:
3x + 3(1 + x) + 5 = 2(3x) + 8
3x + (1 * 3 + x * 3) + 5 = 2(3x) + 8
3x + (3 + 3x) + 5 = 2(3x) + 8

Reorder the terms:
3 + 5 + 3x + 3x = 2(3x) + 8

Combine like terms: 3 + 5 = 8
8 + 3x + 3x = 2(3x) + 8

Combine like terms: 3x + 3x = 6x
8 + 6x = 2(3x) + 8

Remove parenthesis around (3x)
8 + 6x = 2 * 3x + 8

Multiply 2 * 3
8 + 6x = 6x + 8

Reorder the terms:
8 + 6x = 8 + 6x

Add '-8' to each side of the equation.
8 + -8 + 6x = 8 + -8 + 6x

Combine like terms: 8 + -8 = 0
0 + 6x = 8 + -8 + 6x
6x = 8 + -8 + 6x

Combine like terms: 8 + -8 = 0
6x = 0 + 6x
6x = 6x

Add '-6x' to each side of the equation.
6x + -6x = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 6x + -6x

Combine like terms: 6x + -6x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -5t+8=t+56 | | 8+5m=-2m-13 | | 6x+7=-2x+39 | | 6k+2=-3+k | | 5a-6=-69-4a | | 7+5d=4d+17 | | 5m+5=-m+17 | | 4a+6=3a+15 | | 5d-1=d+47 | | -6x+10=6x-50 | | -3+a=6a+47 | | 6t+3=5t+8 | | a+2=-4a-58 | | k+8=-12+6k | | 3X^2-21x+18=0 | | 2x+7x-90=180 | | 7+5t=7t+1 | | 2m-10=-6+4m | | 2k-1=7k-21 | | 2n-10=-7n-1 | | 2(x+6)-10=12 | | 9+5n=4n-2 | | 5m-1=11+m | | 2a-1=-31+7a | | 12/2(1+2) | | 4x-5=-9+6x | | 10-6d=-2d-10 | | -7-4b=-3b+0 | | -2n-3=3n-43 | | 4w-3=-3-6w | | 4+6d=-4d+64 | | -16-18=3 |

Equations solver categories